Leveraging Africa’s underutilized crops to combat climate change, water scarcity, and food insecurity in South Africa - Abiodun Olusola Omotayo; Abeeb Babatunde Omotoso; John Awungnjia Asong (Scientific Reports)
Abstract This study aims to integrate underutilized crops (UCs) into the food system to address climate change impacts, and food -water insecurity. UCs have immense potential to mitigate food shortages, yet their role remains largely unexplored in mainstream agricultural and food security strategies. A multidisciplinary approach using social psychology, resource-based theory (RBT), and a new ecological paradigm was used to investigate factors influencing UCs adoption and their potential contribution to water and food insecurity in South Africa. The water poverty index (WPI) and household food insecurity access score (HFIAS) were used to determine the water and food insecurity status of rural households. The study found that UCs cultivation was driven by awareness, access to extension advisory services, and climate information. The findings indicate that adopting UCs significantly improves water and food insecurity in South Africa. Consequently, households that integrated UCs into their farming systems experienced higher WPI scores, reflecting improved water availability and conservation, as UCs require less water than conventional crops. Likewise, lower HFIAS values suggest that UCs enhance food insecurity by diversifying diets, stabilizing food access, and reducing seasonal hunger. Statistically, households in Limpopo, Mpumalanga, and North-West provinces who adopted UCs saw 25.18 (21%), 31.03 (26%), and 28.77 (24%) rise in WPI and HFIAS compared to those who did not embrace UCs, respectively. These results highlight the potential of UCs as climate-resilient crops that mitigate water scarcity and food insecurity, making them a viable strategy for enhancing rural livelihoods amid climate change. Therefore, prioritizing UCs cultivation could build more resilient agricultural systems, address water scarcity and improve food security.